Experimental Investigation of the Bearing Pressure for Circular and Ring Footings on Sand - Hashim G. Rasheed Al-Sumaiday; Israa S. Hussain Al-Tikrity (Tikrit Journal of Engineering Sciences, 2013)
This paper presents the results of laboratory model tests of bearing pressure of circular and ring footing on sand. The effects of the embedment depth, internal friction of sand and the ratio of the inner to the outer diameter of the ring footing have been studied, in order to understand the behavior of the sand under the ring footing comparing with the circular one. An optimum ratio of the inner to outer diameter of the ring footing have been indicated which was (0.4), at which the bearing capacity will be greater than the circular footing. Also, the results indicated that there was no interested effect of the embedment depth on that optimum ratio.